1998
DOI: 10.1115/1.2792641
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Underfill-Encapsulated Flip-Chips With Heat Spreaders

Abstract: The effect of a heat spreader on the life of the solder joints for underfill-encapsulated, flip-chip packages is investigated through stress analyses and thermal cycling tests. An underfill with suitable mechanical properties is found to be able to prolong the fatigue life of the solder joints even in a package with a heat spreader and an alumina substrate. The delamination of the underfill from the chip is revealed as another critical failure mode for which the shape of the underfill fillet has a large effect. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It is commonly accepted that the dominant failure mode of FCOB assemblies with underfill is delamination of the underfill and the subsequent fracture of solder joints, which has been predicted in some finite element simulations (Madenci et al, 1998) and observed by experimental investigations (Nysather et al, 1998). However, some studies reported that delamination was not observed before the solder joint failure (Doi et al, 1998) and that the failure mechanism changed with improved underfill materials (Gamota and Melton, 1997;Rosson et al, 1999). Finite element simulation also shows that rapid failure of the solder joints can be significantly reduced by using an underfill with a low CTE, high Young's modulus and high Tg, even when a complete delamination occurred (Rzepka et al, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…It is commonly accepted that the dominant failure mode of FCOB assemblies with underfill is delamination of the underfill and the subsequent fracture of solder joints, which has been predicted in some finite element simulations (Madenci et al, 1998) and observed by experimental investigations (Nysather et al, 1998). However, some studies reported that delamination was not observed before the solder joint failure (Doi et al, 1998) and that the failure mechanism changed with improved underfill materials (Gamota and Melton, 1997;Rosson et al, 1999). Finite element simulation also shows that rapid failure of the solder joints can be significantly reduced by using an underfill with a low CTE, high Young's modulus and high Tg, even when a complete delamination occurred (Rzepka et al, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…The chip stress not only depends on fc and Is but also depends on the shape of the under-fill at the edge of the chip [3]. We thus evaluated the dependence on the shape of the under-fill, i.e.. h and I in the FEA model in Fig.…”
Section: Reliability Issuementioning
confidence: 99%
“…under-fills are inserted between the WPPs and the substrate. The reliability of solder joints between the WPP and the substrate is thus very high [3]. To further reduce the cost of the MCM, a low-cost FR-4 base is used a substrate on which the WPPs are mounted.…”
Section: Introductionmentioning
confidence: 99%
“…with the d e f~t i o n of Mises inelastic strain rate p (5) where n is the stress exponent, D the drag stress, &, the reference strain rate, k the Bolmann constant, Q the activation energy for inelastic deformation processes, T the absolute temperature, respectively. However, the Mses equivalent stress G e is defined in different ways, which could be involved in a back stress, depending on specific constitutive model.…”
Section: Nonlinear Materials Models Of Solder and Underfillmentioning
confidence: 99%
“…Currently, most of analyses still use thermal elastic properties of undmfill encapsulants to perform iinite element simulation of Flip-chip package [5] [6][11]. The reason could be the lack of experimental data of nonlinear properties of underfills.…”
Section: Introductionmentioning
confidence: 99%